Ring-like late gadolinium enhancement for predicting ventricular tachyarrhythmias in non-ischaemic dilated cardiomyopathy. (23rd June 2021) - Chen, Wensu; Qian, Wen; Zhang, Xinwei; Li, Dongcheng; Qian, Zhiyong; Xu, Hai; Liao, Shengen; Chen, Xing; Wang, Yao; Hou, Xiaofeng; Patel, Amit R; Xu, Yi; et al.
Abstract: Aims: Myocardial fibrosis is associated with clinical ventricular tachyarrhythmia (VTA) events in patients with non-ischaemic dilated cardiomyopathy (DCM). Subepicardial or mid-wall ring-like late gadolinium enhancement (LGE) has received increasing attention in recent years. The aim of this study was to investigate the relationship between ring-like LGE and VTAs in DCM. Methods and results: Patients diagnosed with non-ischaemic DCM who underwent cardiac magnetic resonance with LGE imaging at baseline were investigated. The composite outcome was the occurrence of VTAs defined as sustained ventricular tachycardia, ventricular fibrillation/flutter, aborted sudden cardiac death (SCD), SCD, and appropriate implantable cardioverter-defibrillator intervention. The final cohort comprised 157 patients, including 36 (22.9%) in no LGE group, 48 (30.6%) in focal LGE group, 40 (25.5%) in multi-focal LGE group, and 33 (21%) in ring-like LGE group. Ring-like LGE group patients were younger compared to focal and multi-focal LGE group ( P < 0.001) with higher left ventricular ejection fraction (33.0% vs. 24.4% vs. 22.1%, P < 0.001). After a median of 13 ± 7 months follow-up, compared to patients with no LGE, the hazard ratios (HRs) with 95% confidence intervals (CIs) for VTAs were 2.90 (0.56–15.06), 5.55 (1.21–25.44), and 11.75 (2.66–51.92) for patients with focal LGE, multi-focal LGE, and ring-like LGE, respectively. After multivariable adjustment, ring-like LGE group remained associated with increased risk of VTAs (adjusted HR 10.00, 95% CI 1.54–64.98; P = 0.016) independent of the global LGE burden Conclusion: The ring-like pattern of LGE is independently associated with an increased risk of VTAs in patients with non-ischaemic DCM.